Practical and self-configurable multihop wireless infrastructure: a functional perspective. (2017) - Alizai, Muhammad Hamad
Multihop wireless networks require self-configurable and reliable communication infrastructure that can quickly adapt itself to the rapidly changing network conditions without manual reconfiguration. The key to developing such a communication infrastructure requires (i) efficient link estimation mechanisms, (ii) reliable routing algorithms, and (iii) stable addressing schemes. In the past decade, a number of practical solutions have been developed for these three main components of multihop wireless infrastructure in inherently similar mesh networks, sensor networks, and MANETs. However, we lack a comprehensive review that classifies these solutions and compares them on the basis of a set of properties desired in wireless networks. In this review, we classify different techniques implemented and evaluated by the research community, define a set of properties, and functionally compare representative techniques from each class.